Platelet-rich plasma (PRP) enhances bone healing in non-united critical-sized defects: a preliminary study involving rabbit models - Kanthan, S.R.; Kavitha, G.; Addi, S.; Choon, D.S.K.; Kamarul, Tunku (Elsevier, 2011)
Introduction: The use of bone grafts in treating non- or delayed unions as the result of large bone loss is well established. However, despite good outcomes, the time to achieve complete union is still considerably long. To overcome this problem, the use of platelet-rich plasma (PRP) has been advocated albeit with varying success. To determine the true effectiveness of PRP in treating non-/delayed unions, a study was conducted using (n = 12) rabbit models. Methods and materials: Critical-sized defects measuring 2 cm created in the midshaft of the right rabbit tibias were stabilised using 2.7-mm small fragment plates. A spacer placed in the defects to create a delay in bone union was replaced at 3 weeks with artificial bone grafts (Coragraft (R)), with or without PRP. The operated limbs were radiographed following the defect creation and at 3, 7 and 11 weeks (at sacrifice). Bone healing and histological changes were later assessed and scored using the appropriate grading systems. Four groups were compared for quality of healing: (group-A) control group, that is, no PRP or Coragraft; (group-B) PRP; (group-C) Coragraft; and (group-D) PRP and Coragraft. Results: Group-D demonstrated the best bone healing based on radiological, histological and gross findings (Kruskall-Wallis: p < 0.05). Group-C had significantly higher scores than group-B, whilst group-A had significantly lower scores than all other groups (Mann-Whitney U: p < 0.05). Conclusion: The use of PRP with bone graft significantly improves the quality of bone healing. However, the use of PRP without bone substitute does not provide adequate repair tissue and, therefore, provides little benefit when used independently. (C) 2011 Elsevier Ltd. All rights reserved.